Unraveling the cause of an aircraft accident. (March 2019) - Sujata, M.; Madan, M.; Raghavendra, K.; Jagannathan, N.; Bhaumik, S.K.
Abstract: An investigation of a twin-engine fighter aircraft accident has been reported. The accident was caused due to fuel leakage. The primary failure which led to the fuel leakage and the subsequent accident to the aircraft was identified. The failure involved fatigue fracture in a pipeline supplying fuel to the hydraulic cylinder for jet nozzle operation of one of the engines. Although the identification of the primary failure was successful, further analysis in establishing the cause of the failure of the pipeline, and the time duration over which the failure occurred, raised several questions. These questions needed to be answered by the failure analysts for enabling the investigating committee to proceed further with the investigation. Through a detailed fractography study in conjunction with the fracture-mechanics-based calculations, the fracture process in the pipeline was explained. Following this, further metallurgical studies on the failed pipeline were planned for unraveling the primary cause that led to the accident. It was established that excessive softening of the material during the brazing operation was responsible for the premature fatigue crack initiation in the pipeline. Since the accident had serious implications on the manufacturer as well as the operator, the failure analysts had to overcome several hurdles during the course of the investigation. The investigation presented in this article is an example of how systematic approach to a failure can help in bringing out the truth in conflicting situations. Highlights: A fighter aircraft accident was investigated to find out the cause. Leakage from one of the fuel pipelines due to fatigue fracture was responsible for the accident. The softening of the pipeline material during the brazing operation was the cause of the fatigue crack initiation.